Fourth Five-Year Plan Madras State Annual Plan for 1968-69 Narrative Notes on Important Schemes - Planning Commission (Planning Commission, 1968)
The object of the scheme is to establish state seed farms for the production of foundation (Primary) seeds. It has been estimated that a total of 230 State Seed Farms, in units of 25 acres each, 2 will be sufficient for the production of the Primary Paddy and Millet Seeds required to produce secondary seeds to cover one-third of the area under these crops in the State every year. By the end of the Second Plan period, 134 units were established. During the Third Plan period, another 66 units were established bringing the total to 200 units.
Government of Madras